(untitled) (University Heart Journal, 2020)
Assessment is a systematic procedure for measuring a trainee’s progress or level of achievement against defined criteria, in order to make a judgement about the trainee. It includes traditional exam-style questions, multiple choice questions (MCQs), viva voce examinations, assessments of performance carried out in real time. The purpose of assessment include diagnosing learning needs, motivating learners and to determine entry to a course or profession. Traditional examinations are often used to measure the candidates to recall previously learned knowledge, but may not correlate well with a person’s workplace based performance. Workplace based assessments (WBA) are much better suited to providing an indication of actual performance in the workplace. University Heart Journal Vol. 16, No. 2, Jul 2020; 106-110